Influencing pathways of mountain-waters project pilot policy on corporate ESG in China - Honggen, Zhu; Jianjun, Li; Limin, Zhang (Frontiers in Environmental Science, 2025)
Introduction:Although considerable research has explored factors affecting corporate ESG performance and environmental policies, few studies integrate these dimensions to assess the Mountains-Waters Project pilot policy—an expansive ecological restoration initiative in China. This study aims to examine the policy's effects on corporate ESG performance within the Yangtze River Economic Belt, a critical ecological and economic region in China.Methods:To investigate the effects of the pilot policy, we use panel data from 129 publicly listed companies across 76 districts (2009—2023). A multi-period difference-in-differences (DID) model is employed to analyze the impact of the policy on corporate ESG performance.Results:The findings show that the pilot policy significantly enhances corporate ESG performance. The effects operate through three primary mechanisms: promoting green technologies, boosting media attention, and strengthening government oversight of environmental practices. Furthermore, the effects are more pronounced for high-tech and non-state-owned enterprises, suggesting heterogeneous responses to policy interventions.DiscussionThese results provide novel empirical evidence on the role of environmental policies in advancing corporate sustainability. They also offer valuable insights for the design and implementation of future policies, especially in regions with significant ecological and economic importance like the Yangtze River Economic Belt.